PENYELENGGARAAN PENDIDIKAN MADRASAH DINIYAH TAKMILIYAH DI PONOROGO - Moch. Djahid (Universitas Muhammadiyah Ponorogo, 2016)
Madrasah Diniyah Takmiliyah is one of non-formal Islamic religious education institutions organized in a structured and tiered as a complement to the implementation of the religious educations, whose the students come from the learners of formal educations (SD/MI, SMP/MTs and SMA/MK) with the aim to increase and enrich the religious knowledge. This research was written in the quantitative descriptive and the data were collected by interview and documentations. In Ponorogo district, there were 523 Madrasah Diniyah Takmiliyah educational institutions, 49.364 students and 4812 teachers spreading over 280 villages, 21 sub-districts, and 102 boarding schools in 18 sub-districts. The educational curriculum system used a unified principle for its policy and diversity in the implementation. Most of the teachers (2995 - 69,8%) were still graduated of senior high school, some of them had been using scholarship program given by East Java governor. The scholarship had been given since 2012 – 2013, 2013 – 2014, 2014 – 2015 and 2015 – 2016, working together with Islamic State/Private University in East Java. One of university was Islamic Religious Faculty of Muhammadiyah University of Ponorogo. The data above showed that the attention of Ponorogonese people towards Islamic education was very high, for those, Ponorogo is called Kota Santri.